Effect of metabolic control on the in vitro proliferation of peripheral blood mononuclear cells in type 1 and type 2 diabetic patients - Foss-Freitas, Maria Cristina; Foss, Norma Tiraboschi; Donadi, Eduardo Antonio; Foss, Milton Cesar (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Diabetes mellitus is a clinical syndrome that frequently leads to the development of chronic complications and high susceptibility to infections. It is probably due to defective immunological defense, which may be related to metabolic control of the disease. The aim of this study was to evaluate the effect of metabolic control on immune-cell behavior in type 1 and type 2 diabetic patients. For this, the in vi- tro proliferation of peripheral blood mononuclear cells (PBMC) was analyzed in patients with inad- equate and adequate metabolic control. DESIGN AND SETTING: Experimental/laboratory study at a university hospital. METHODS: Eleven type 1 and thirteen type 2 diabetic patients were studied, together with 21 healthy individuals divided in two groups (11/10), who were matched by sex and age with those diabetic patients. PBMC cultures stimulated with concanavalin-A (Con-A) were used to measure 3H-thymidine incorporation after 72 hours of cell culturing. For patients with inadequate metabolic control, culturing was per- formed on the first day of patient hospitalization and again after intensive treatment to achieve adequate control. RESULTS: The proliferation index for Con-A-stimu- lated cultures from type 1 diabetic patients was significantly greater than that for cultures from healthy individuals and type 2 diabetic patients, independent of metabolic control. A negative cor- relation between the proliferation cell index and body mass index and serum C-reactive protein levels was also observed. CONCLUSION: The increase in the prolifera- tion capacity of type 1 diabetic T lymphocytes was probably not caused by hyperglycemia and/or insulinopenia related to inadequate metabolic control.